Can newborn infants with positive HIV soon after birth be diagnosed with intrauterine infection? - Yuqian Luo; Yi-Hua Zhou; Hong Zhao (Elsevier, 2023)
Background: Mother-to-child transmission (MTCT) of human immunodeficiency virus (HIV) can occur intrauterine, intrapartum, and postpartum. Currently, infants with confirmed positive results in virological tests before 48 h of age are defined as having intrauterine infection. Aim: We herein review the literature that identifies emerging challenges in diagnosing intrauterine HIV infection to rethink the current diagnostic criteria. Findings: A number of reports have shown that some infants who were diagnosed with intrauterine HIV infection after birth became negative for HIV in the subsequent follow-ups, including negative HIV antibodies at the age of 12-18 months. Such ''clearance'' of HIV was attributed to various reasons: neonatal antiretroviral treatment (ART), false positivity, strong host immune response, or unknown factors in maternal breast milk. Discussions: Positive HIV tests in newborn infants shortly after birth do not necessarily indicate HIV infection, because maternal HIV can enter fetal circulation intrapartum due to the repetitive, strong uterine contractions. The infants are therefore exposed to, but may not yet be infected with HIV at that time. The current diagnostic criteria cannot differentiate HIV exposure from HIV infection, leading to so-called "challenges in diagnosing intrauterine HIV infection". Those infants diagnosed with intrauterine infection who cleared HIV later were less likely to have been truly infected with HIV, but more likely to have been exposed to HIV. Moreover, we suggest that the determination of HIV antibody titers in infants' serial serum samples can provide valuable information to distinguish intrapartum exposure from intrauterine infection.